An Islamic Counseling Approach Rooted in Tazkiyatun Nafs: A Tafsir Analysis of Seven Qur’anic Verses - Eli Zerni; Hasan Zaini; Irman Irman (The Future of Education Journal, 2026)
This study aims to analyze the concept of tazkiyatun nafs based on the interpretation of selected Qur’anic verses and to examine its implications for Islamic guidance and counseling. The study is motivated by the need for integrative counseling approaches that incorporate both psychological and spiritual dimensions. This research employs a qualitative approach using the Systematic Literature Review (SLR) method by synthesizing relevant sources from Scopus-indexed journals, SINTA-accredited national journals, and classical and contemporary Qur’anic exegesis. The analysis focuses on seven Qur’anic verses, namely At-Tawbah (9:103), An-Nur (24:21), Fatir (35:18), An-Najm (53:32), Al-Jumu’ah (62:2), Ash-Shams (91:9), and Al-A‘la (87:14–15). The findings reveal that tazkiyatun nafs represents a holistic process of self-purification encompassing six major dimensions: intrapersonal, social, preventive, personal responsibility, educational, and transcendental. These dimensions are aligned with contemporary psychological constructs such as self-regulation, emotional regulation, and meaning in life. Furthermore, this study formulates an integrative framework for Islamic counseling based on Qur’anic values, providing both theoretical and practical contributions to the development of spiritually grounded counseling approaches in addressing contemporary mental health challenges.